Empowering inclusive education through the design of supportive outdoor spaces - Dian Kartika Santoso; Rizka Tiara Maharani; Umi Safiul Ummah (Journal of Community Service and Empowerment, 2025)
This community service project was conducted to address the limited inclusivity and accessibility of outdoor learning environments at SLB YPAC Surabaya, a special needs school in Indonesia. The objective was to design inclusive front yard and central courtyard spaces that support educational, therapeutic, and social activities for students with diverse disabilities. The project provided the school with two conceptual, ready-to-implement design proposals developed through a participatory process. A qualitative, participatory approach was used, involving site observations, spatial analysis, and a Focus Group Discussion (FGD) with school stakeholders. Data gathered informed design solutions based on universal design principles and multisensory accessibility. The front yard design includes guiding blocks, inclusive waiting areas, and accessible circulation routes, while the central courtyard features a multisensory interaction zone with rubber flooring, therapeutic paths, tactile walls, and shaded resting areas. Both designs address key accessibility, comfort, and learning needs identified through FGD. This project shows that inclusive spatial planning, even without physical implementation, can generate practical and meaningful outcomes. The designs not only align with universal design theory but also reflect the real needs of users, offering a foundation for inclusive educational infrastructure that can be replicated in similar school contexts.